PEMBERIAN PINJAMAN KREDIT SECARA ONLINE MELALUI SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN THE SATISFICING MODEL DI PT. BFI FINANCE INDONESIA CIREBON - Anita Anita; Nana Suarna (Masoem University, 2018)
The existence of the internet today provides benefits directly or indirectly to the business world, education, community and more, from small to large scale. With the internet facility data can be stored, retrieved and sent easily to all directions. So can not be denied the existence of internet website becomes the main requirement in providing the fastest information in globalization today. In the creditworthiness assessment conducted by PT. BFI Finance Indonesia Cirebon is still experiencing difficulties. The presentation of credit lending information is often delayed. One form of utilization of this facility is by making Decision Support System Online Loan Disbursement Using The Satisficing Model. This system will be used to analyze the personality and income of a person who will perform vehicle loans. By using this analytical method is expected to generate and simplify the process of acceptance of creditor candidates in accordance with the expected criteria so as to streamline the cost and time.